Dynamic analysis of RMB-ASEAN exchange rate under the background of the Belt and Road Initiative - Rong Li, Hong Chen, Shilei Xiang (Forest Chemicals Review)
The proposal of the Belt and Road strategy provides a win-win option for developing countries. However, with the increasing complexity of the international environment, the risk of uncertainty has also seriously affected the normal order of the economic environment. Under this background, through the construction of a TVP-SV-VAR model of geopolitical risks, economic policy uncertainty and RMB exchange rate changes, the dynamic time-varying of the RMB-ASEAN exchange rate is analyzed. The results show that geopolitical risks and economic policy uncertainties have obvious long-term effects on exchange rate fluctuations in the sample countries, and are roughly positive in the short term, and the impact is the most significant after the Belt and Road Initiative was put forward.